Impact of ferrite materials on wireless power transfer efficiency for electric vehicles battery chargers - Wan Muhamad Hakimi Wan Bunyamin; Rahimi Baharom (Institute of Advanced Engineering and Science, 2026)
This paper investigates the impact of ferrite materials on the efficiency of wireless power transfer (WPT) systems designed for electric vehicle (EV) and E-bike battery chargers. The study employs 3D full-wave electromagnetic simulations in CST Studio Suite 2024 to evaluate how Laird Performance Materials 33P2098-0M0 ferrite influences magnetic coupling, field confinement, and overall transfer efficiency. Two configurations were analyzed: coil-only and coil-with-ferrite plates, under a fixed 20 mm air gap and an operating range of 30–50 kHz. The inclusion of ferrite materials significantly improved magnetic-flux directivity and coupling strength, resulting in a peak efficiency of 99.21% at 41.3 kHz, compared to 99.09% at 38.1 kHz for the coil-only design. The enhanced configuration also reduced magnetic leakage and improved resonance stability, as verified through mesh-independent simulations and analytical validation with less than 2% error. The proposed model correlates ferrite permeability with mutual inductance and resonant-frequency tuning, confirming the theoretical basis of the efficiency gain. This work bridges a gap in small-scale EV and E-bike WPT research by quantifying the measurable benefits of ferrite integration and providing design guidelines for compact, thermally stable, and high-efficiency wireless charging systems.